النظام اللغوي و ومقتضى الحال و أثرهما في نجاح العملية الاتصالية التواصلية عند الجاحظ من خلا كتابه البيان والتبيين (مجلة الواحات للبحوث والدراسات, 2021)
The reseach concerning the Arab heritage is an important issue, especially if it is related to a distinguished and a prominent scholar such as Al-Jhaiz, whose works and writings are characterized by excellence, skill, mastery and sophisticated intelligence. He is considered to be a man of knowledge and science, specifically when it comes to rhetorics. As he has a crucial role in giving it interest and granting it a distinguished place.What we aim at in this study is to search a case that we found features related to Al-Jahiz, it is the linguistic system and the appropriatenessof the  case and their impact on the success of the communicative process at Al-Jahiz through his book Al-Bayan and Al-Tabin. key words  -  Appropriateness of the  case -linguistic system – Communication- Connection- concerning -Al-Jahiz